Attitude of Haor Farmers’ Towards Extension Services - Das, S; Haque, ME; Rokonuzzaman, M; Saha, S; Saha, SR (Annals of Bangladesh Agriculture, 2022)
The study was to determine haor farmers’ attitude towards extension services provided by extension agents in haor area. The study was conducted in Austagram upazila under Kishoregonj district during June to August 2018. Data were collected randomly from 150 haor farmers through face to face interview using an interview schedule. Majority (62%) of the respondents had moderately favorable attitude towards extension service provided by extension agent followed by 26 percent had slightly favorable attitude and only 12 percent showed highly favorable attitude. Extension agents provided enough motivational tour, rice production based training and demonstration effectively. Majority (78%) of the respondents strongly agreed with that ‘Teaching tools (Leaflet, Poster, Demonstration) used by extension agent are very effective.’ The farmers were acutely aware of the benefits and profitability of the extension services. However, 46 percent of the respondents strongly agreed with that ‘Resource-rich farmers get more benefit of extension services than others’. The selected characteristics like, annual income (χ2 value=11.61*), training exposure (χ2 value=15.65*), education level (χ2 value=12.97*) and living distance from upazila headquarter (χ2 value=10.64*) had significant associations with their attitude towards extension services provided by extension agent. The further extension services suggested by the farmer were i) set up local extension office in their union, ii) arranging training based on their problem, iii) make available low cost combine harvester, seed sowing machine and other necessary agricultural equipment’s, iv) extending communication equally for all categories of farmers’ and v) increase number of demonstrations on new high yielding rice varieties. Ann. Bangladesh Agric. (2021) 25 (2) : 61-75